2017
DOI: 10.1007/s10571-017-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functional MicroRNA-186-5p Targets both FGF2 and RelA to Suppress Tumorigenesis of Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is one of the most malignant cancers. MicroRNAs (miRs) were reported to play important roles in GBM recently. However, the role of a novel miR-186-5p in GBM tumorigenesis is still elusive. Using bioinformatics, miR-186-5p was identified as potential regulators of both fibroblast growth factor (FGF)-2 and NF-κB subunit RelA. Luciferase reporter assay was used to confirm the direct recognition FGF2 and RelA mRNAs by miR-186-5p. Invasion and migration assays were employed to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…By targeting YAP1, miR-186 inhibited proliferation, migration, and invasion of pancreatic cancer (31) and hepatocellular carcinoma cells (32). Moreover, miR-186 repressed invasion and migration by directly targeting TBL1XR1 and FOXK1 in osteosarcoma cells (52,53), or targeting FGF2 and RelA in glioblastoma multiforme cells (43). MiR-186 inhibited proliferation of human pituitary tumor cells through targeting SKP2, thus upregulating p27 Kip1 expression, a well-known negative regulator of G1 cell cycle progression (44).…”
Section: Mir-186 As a Tumor Suppressor Mirnamentioning
confidence: 99%
“…By targeting YAP1, miR-186 inhibited proliferation, migration, and invasion of pancreatic cancer (31) and hepatocellular carcinoma cells (32). Moreover, miR-186 repressed invasion and migration by directly targeting TBL1XR1 and FOXK1 in osteosarcoma cells (52,53), or targeting FGF2 and RelA in glioblastoma multiforme cells (43). MiR-186 inhibited proliferation of human pituitary tumor cells through targeting SKP2, thus upregulating p27 Kip1 expression, a well-known negative regulator of G1 cell cycle progression (44).…”
Section: Mir-186 As a Tumor Suppressor Mirnamentioning
confidence: 99%
“…Remarkably, in human THP-1 macrophages miR-186 enhances secretion of IL-6, IL-1β and TNF-α as well as lipid accumulation via targeting cystathionine-γ-lyase ( CSE ) [217]. Moreover, in human glioblastoma cells FGF2 and the NF-κB subunit RelA have been identified as miR-186 targets [218]. Summarized, despite induction of inflammatory cytokine expression by miR-186, the inflammatory response is apparently attenuated via NF-κB depletion.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…A study demonstrated that RELA is a mediator of oncogene of pancreatic ductal adenocarcinoma, and the bene cial effects of RELA were mediated by increased expression of CXCL1 and CXCR2 23 . NFKB1 as a suppressor of the NF-κB response contributed to tumorigenesis in many types of cancer, including GBM 24 . The cumulative data demonstrated CXC chemokine and NF-κB pathway may become potentially molecular targets in the clinical treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%